2023
DOI: 10.1055/a-2184-7506
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Incident Atrial Fibrillation and Subsequent Use of Oral Anticoagulants in Patients with Dementia

Chuan-Tsai Tsai,
Yi-Hsin Chan,
Jo-Nan Liao
et al.

Abstract: Background: Dementia and atrial fibrillation (AF) have many shared risk factors. There are limited data on the risks of incident AF and AF-related clinical outcomes in patients with dementia. Methods: Out study utilized the Taiwan National Health Insurance Research Database. A total of 544,074 patients with dementia were compared to 554,074 age- and sex-matched patients without dementia regarding the risk of incident AF. Among patients with dementia who experienced incident AF, the risks of clinical events of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Evidence suggests that anticoagulation may protect against or slow the progression of cognitive impairment by reducing silent brain infarctions or microemboli; rhythm control strategies may also be useful in this regard [60]. In the previously mentioned study by Tsai et al, for patients with dementia who experienced new-onset AF, NOAC use was associated with a better clinical outcome compared with no anticoagulation [59]. This is important, as patient with cognitive impairment may be less able to report symptoms of AF or be less considered for NOAC use by treating physicians due to a perceived lower AF burden.…”
Section: Af Burden Beyond Stroke Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that anticoagulation may protect against or slow the progression of cognitive impairment by reducing silent brain infarctions or microemboli; rhythm control strategies may also be useful in this regard [60]. In the previously mentioned study by Tsai et al, for patients with dementia who experienced new-onset AF, NOAC use was associated with a better clinical outcome compared with no anticoagulation [59]. This is important, as patient with cognitive impairment may be less able to report symptoms of AF or be less considered for NOAC use by treating physicians due to a perceived lower AF burden.…”
Section: Af Burden Beyond Stroke Riskmentioning
confidence: 99%
“…In addition, recent evidence suggests that AF and cognitive impairment may be downstream events of atrial cardiomyopathy, which is in turn caused by metabolic syndrome and obesity, suggesting that cardiovascular and metabolic comorbidities may be mediators of the association between AF and cognitive impairment [58]. Tsai and colleagues also found that patients with dementia compared to patients without dementia had a higher risk of incident AF, suggesting a possible bidirectional relationship [59]. Evidence suggests that anticoagulation may protect against or slow the progression of cognitive impairment by reducing silent brain infarctions or microemboli; rhythm control strategies may also be useful in this regard [60].…”
Section: Af Burden Beyond Stroke Riskmentioning
confidence: 99%
See 1 more Smart Citation